ANALISIS RASIO KEUANGAN UNTUK MEMPREDIKSI KONDISI FINANCIAL DISTRESS PERUSAHAAN PULP DAN KERTAS YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2017 DENGAN MODEL ALTMAN Z-SCORE - Sari, Maya; Diana, Haugesti (Research in Accounting Journal (RAJ), 2020)
Identification conditions of financial difficulties is more important than bankruptcy, because companies will surely experience financial distress conditions first and then go bankrupt. This studi aims to examine the effect of the Current Ratio (QR), Quick Ratio (QR), Debt to Equity Ratio (DER), Return On Assets (ROA), and sales growth on the financial distress conditions of the pulp and paper subsector companies listed on the indonesi stock exchange from 2012 to 2017. This study use a quantitative approach. The study population included all pulp and paper subsector companies listed on the Indonesia stock exchange from 2012 to 2017, namely 8 companies. The sample was determined by purpose sampling technique. Data analysis method used is logistic regression analysis. The results of thr study showed that the best performance of the company with the lowest level of bankruptcy was PT. Kedawung Setia Industrial Tbk. From the results of testing multiple linear regression obtained Roa has a significant effect on the condition of financial distress. Whereas CR, QR, DER and Sales Growth do not effect the financial condition of the distress.